GEO and sustainable performance: the moderating role of GTD and environmental consciousness - Ong, Tze San; Latif, Badar; Di Vaio, Assunta (Emerald Publishing, 2022)
Purpose: Congruent with the world-wide call to combat global warming concerns and advance intellectual capital (IC), organisations are being pressured to ensure that IC is managed effectively to encourage green initiatives. In this regard, green entrepreneurial orientation (GEO) is emerged as a relevant IC. GEO is recognised as a mitigating factor of environmental degradation in the literature. Although prior literature has observed the nexus between GEO and firm performance, the role of GEO in leveraging sustainable performance has been limitedly explored. This study explored the relationship between IC as a GEO and enterprises' sustainable performance through the moderating roles of environmental consciousness and green technology dynamism (GTD) in the context of two developing countries (Pakistan and Malaysia). Design/methodology/approach: Data provided by 296 respondents from 264 manufacturing small and medium-sized enterprises (SMEs) in Pakistan and Malaysia were analysed through a three-wave research design. AMOS 23 software was used to perform covariance-based structural equation modelling (CB-SEM), while hierarchical regression analysis was applied using the SPSS 25 software to examine the causal relationships in the model. Findings: IC as a GEO significantly influences sustainable performance, akin to environmental consciousness and GTD. Besides, GTD has a significant moderating effect between GEO and financial and environmental performance in Pakistan and Malaysia but not between GEO and social performance. Environmental consciousness has a significant moderating role in the impact of GEO on financial performance in Pakistan and Malaysia, but not on social and environmental performance. Practical implications: The study's findings are useful for managers of Pakistani and Malaysian manufacturing SMEs to identify ways to encourage GEO to improve sustainable performance in their firms. The findings suggest that managers should effectively implement GTD and environmental consciousness to strengthen the GEO and sustainable performance relationship. Managers can use GEO concretely as a reference for the companies that intend to support the United Nation SDG-2030 agenda and to find new business opportunities for the implementation of sustainable development. Originality/value: To the best of the authors' knowledge, this study is the first to examine the link between GEO and sustainable performance in developing countries such as Pakistan and Malaysia. Although the influence of various intangible assets or IC on sustainable performance has been widely examined in the literature, the role of GEO as IC has been limitedly explored. This study extends the literature by adding to the knowledge of GEO as a form of firms' IC that enhances boundary conditions in developing countries.